2013 IEEE Conference on Computer Vision and Pattern Recognition 2013
DOI: 10.1109/cvpr.2013.394
|View full text |Cite
|
Sign up to set email alerts
|

Manhattan Junction Catalogue for Spatial Reasoning of Indoor Scenes

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 25 publications
(41 reference statements)
0
56
0
Order By: Relevance
“…This sparked a renaissance during which progress started being made on a variety of long-standing 3D understanding problems. In the indoor world, a great deal of effort went into developing constrained models for the prediction of room layout [10] as well as features [6,23,27] and effective methods for inference [4,22,31,32]. While these high-level constraints have been enormously successful in constrained domains (e.g., less cluttered scenes with visible floors such as the datasets of [10,38]), they have not been successfully demonstrated on highly cluttered scenes such as the NYU v2 Depth Dataset [33].…”
Section: Related Workmentioning
confidence: 99%
“…This sparked a renaissance during which progress started being made on a variety of long-standing 3D understanding problems. In the indoor world, a great deal of effort went into developing constrained models for the prediction of room layout [10] as well as features [6,23,27] and effective methods for inference [4,22,31,32]. While these high-level constraints have been enormously successful in constrained domains (e.g., less cluttered scenes with visible floors such as the datasets of [10,38]), they have not been successfully demonstrated on highly cluttered scenes such as the NYU v2 Depth Dataset [33].…”
Section: Related Workmentioning
confidence: 99%
“…Under the Manhattan world assumption, an efficient voting scheme was introduced recently for computing the junc- tion features [22]. In our work, we use these junction features for designing the penalty terms in the LP.…”
Section: Junction-breaking Costsmentioning
confidence: 99%
“…Jain et al [15] used connectivity constraints for reconstructing lines from multiple images. Recently, it was shown that junction features can be extracted from real images using an efficient voting scheme [22]. We use junctions for designing penalty terms in a linear programming (LP) formulation.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Flint et al [27] addressed the spatial layout estimation problem by integrating information from image features, stereo features, and 3-D point clouds in a MAP optimization problem, which is solved using dynamic programming. Ramalingam et al [28] presented a method to detect junctions formed by line segments in three Manhattan orthogonal directions using a voting scheme. Possible cuboid layouts generated from the junctions are evaluated using an inference algorithm based on a conditional random field model.…”
Section: Related Workmentioning
confidence: 99%